The Shock Index is not accurate at predicting outcomes in patients with upper gastrointestinal bleeding. Issue 2 (23rd October 2019) - Saffouri, Eliana; Blackwell, Clare; Laursen, Stig B.; Laine, Loren; Dalton, Harry R.; Ngu, Jing; Shultz, Michael; Norton, Rebecca; Stanley, Adrian J.
Summary: Background: Acute upper gastrointestinal bleeding (UGIB) remains a major cause of hospital admission worldwide. The recent UK National Confidential Enquiry into Patient Outcome and Death (NCEPOD) report on severe gastrointestinal bleeding used the Shock Index to assess bleeding severity and found an association between Shock Index and mortality. However, this has never been prospectively validated as a predictor of outcome in UGIB. Aims: To compare the Shock Index with existing pre‐endoscopic UGIB risk scores in predicting outcomes after UGIB Methods: In an international, prospective study of 3012 consecutive patients with UGIB, we compared the Shock Index with existing scores including the Glasgow Blatchford score (GBS), admission Rockall score, AIMS65, and the newly described "ABC" score. Pre‐determined endpoints were need for major (≥4 units red cells) transfusion, need for endoscopic therapy and 30‐day mortality. Results: The Shock Index was inferior to the GBS in predicting need for major transfusion (area under the receiver operator characteristic curve [AUROC] 0.655 vs 0.836, P  < 0.001) and need for endotherapy (AUROC 0.606 vs 0.747, P  < 0.001). The Shock Index was inferior to all other scores for 30‐day mortality: for example, AUROC 0.611 vs 0.863 for ABC score ( P  < 0.001). Adding the Shock Index to the ABC score did not improve accuracy of the ABC score in predicting mortality (AUROC 0.864 vs 0.863, P  = 0.95). Conclusion: The Shock Index performed poorly with AUROCs <0.66 and was inferior to existing pre‐endoscopy scores at predicting major clinical endpoints after UGIB. We found no clear evidence that the Shock Index is clinically useful at predicting outcomes in UGIB. [Correction added on 20 December 2019, after first online publication: Summary section has been changed for clarification.] Abstract : LINKED CONTENT This article is linked to Bardou and Barkun and McPherson and Hammond and Stanley papers. To view these articles, visit https://doi.org/10.1111/apt.15574 and https://doi.org/10.1111/apt.15615 and https://doi.org/10.1111/apt.15605 .